2023
DOI: 10.1002/lol2.10326
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mismatch between the theory and application of photosynthetic quotients in aquatic ecosystems

Abstract: Accurate measures of primary production in aquatic ecosystems are necessary to quantify energy availability to higher trophic levels and biological effects on global CO 2 concentrations, among other reasons. However, we commonly measure primary production using O 2 because it is easier than measuring changes in CO 2 and the subsequent modeling of the full carbonate system. Although we measure O 2 we are often more interested in the rate of fixed C, and thus use the photosynthetic quotient (the ratio of O 2 rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 75 publications
2
6
0
Order By: Relevance
“…Deviations from the theoretical 1 : 1 relationship between F O 2 and F DIC (Fig. 3d) are thus ubiquitous in the literature (e.g., Barron et al, 2006;Turk et al, 2015;Trentman et al, 2023). In fact, the slope we observed is identical to what Pinardi et al (2009) observed in sediments vegetated with the freshwater macrophyte Vallisneria spiralis using sediment cores.…”
Section: Carbon and Oxygen Balancesupporting
confidence: 78%
See 2 more Smart Citations
“…Deviations from the theoretical 1 : 1 relationship between F O 2 and F DIC (Fig. 3d) are thus ubiquitous in the literature (e.g., Barron et al, 2006;Turk et al, 2015;Trentman et al, 2023). In fact, the slope we observed is identical to what Pinardi et al (2009) observed in sediments vegetated with the freshwater macrophyte Vallisneria spiralis using sediment cores.…”
Section: Carbon and Oxygen Balancesupporting
confidence: 78%
“…Converting these fluxes into carbon currency often relies on assuming a constant stoichiometric 1 : 1 ratio between oxygen and dissolved inorganic carbon (O 2 : DIC) fluxes which may significantly under-or overestimate actual metabolism (e.g., Barron et al, 2006;Duarte et al, 2010;Turk et al, 2015). For marine sediments, this ratio has been estimated to range between 0.8-1.2 on annual timescales (Glud, 2008, and references therein), but the variability is poorly constrained and likely higher in seagrass systems and on shorter timescales (Turk et al, 2015;Trentman et al, 2023). The discrepancy from a 1 : 1 ratio between benthic oxygen and DIC fluxes can stem from a wide range of processes, including anaerobic sediment processes, nitrate assimilation, photorespiration, and differences in solubility and air-sea gas exchange rates between O 2 and CO 2 (Weiss, 1970;Trentman et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assumed that NEP was spatially constant throughout the stream network. We assumed a respiratory quotient of 1 mol C to 1 mol O to convert these oxygen‐based estimates to carbon equivalents, although we acknowledge that this quotient likely varies (Trentman et al., 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Non-specific oxygen consuming process (e.g., microbial respiration, geochemical reactions, gas ebullition) can interfere with measurements. Furthermore, the ratio of oxygen produced to carbon fixed (i.e., photosynthetic quotient) varies significantly between species and physiological conditions (e.g., 0.1 -4.2) introducing large error and uncertainty (Trentman et al, 2023).…”
Section: Introduction 36mentioning
confidence: 99%